MIMO SYSTEM THROUGHPUT EVALUATION SOFTWARE - Одарченко, Р. С.; Ткаліч, О. П.; Креденцар, С. М. (Science-based technologies, 2013)
The work is devoted to developing an effective methodology for assessing the rate of transmission channels in a MIMO antenna system, depending on the type of terrain, the number and nature of obstacles, heights of suspension for receiving and transmitting antennas, radio signal frequency, the width of the used frequency band, MIMO antenna system configuration, etc. On the basis of the proposed methodology for calculating MIMO antenna system bandwidth the specialized software written in C + + has been proposed, which allows setting the bandwidth according to all the parameters considered in the valuation method of MIMO antenna systems with possible using of different frequency bands and various propagation models for prediction of radio signal power loss value.